IDF Diabetes Atlas: global, regional and country-level diabetes prevalence estimates for 2021 and projections for 2045 - Sun, Hong; Saeedi, Pouya; Karuranga, Suvi; Pinkepank, Moritz; Ogurtsova, Katherine; Duncan, Bruce B.; Stein, Caroline; Basit, Abdul; Chan, Juliana C. N.; Mbanya, Jean Claude; Pavkov, Meda E.; Ramachandaran, Ambady; et al. (Diabetes research and clinical practice, 2022)
Aims - To provide global, regional, and country-level estimates of diabetes prevalence and health expenditures for 2021 and projections for 2045. - Methods - A total of 219 data sources meeting pre-established quality criteria reporting research conducted between 2005 and 2020 and representing 215 countries and territories were identified. For countries without data meeting quality criteria, estimates were extrapolated from countries with similar economies, ethnicity, geography and language. Logistic regression was used to generate smoothed age-specific diabetes prevalence estimates. Diabetes-related health expenditures were estimated using an attributable fraction method. The 2021 diabetes prevalence estimates were applied to population estimates for 2045 to project future prevalence. - Results - The global diabetes prevalence in 20-79 year olds in 2021 was estimated to be 10.5% (536.6 million people), rising to 12.2% (783.2 million) in 2045. Diabetes prevalence was similar in men and women and was highest in those aged 75-79 years. Prevalence (in 2021) was estimated to be higher in urban (12.1%) than rural (8.3%) areas, and in high-income (11.1%) compared to low-income countries (5.5%). The greatest relative increase in the prevalence of diabetes between 2021 and 2045 is expected to occur in middle-income countries (21.1%) compared to high- (12.2%) and low-income (11.9%) countries. Global diabetes-related health expenditures were estimated at 966 billion USD in 2021, and are projected to reach 1,054 billion USD by 2045. - Conclusions - Just over half a billion people are living with diabetes worldwide which means that over 10.5% of the world’s adult population now have this condition.
Online verfügbar 6 Dezember 2021
Gesehen am 02.02.2023